Testing The Role Of Country Of Origin, Celebrity Endorser, Ads And E-Wom Towards Consumer Buying Interest - Amir Abdul Karim; Budi Istiyanto (Fakultas Bisnis, 2020)
This research is motivated by the increasing market share of OPPO Smartphones in Indonesia in the Second Quarter of 2019. It is thought that this increase has an effect on increasing sales of the OPPO Smartphone and also makes the reason OPPO Smartphones are able to overtake Samsung's position in Indonesia. The purpose of this study is to analyze the variables Country of Origin, Celebrity Endorser, Advertising and E-WOM on Purchase Interest of OPPO Smartphone products. The research method used is quantitative research. Determination of the number of samples using non-probability sampling techniques with a purposive sampling method with a total sample of 126 respondents. This study uses multiple linear regression analysis. The results of the study indicate that the Country of Origin, Advertisements and E-WOM variables have a positive and significant effect on buying interest in OPPO Smartphone products. While the Celebrity Endorser variable does not significantly influence the buying interest of OPPO Smartphone products.